Immunotherapy targeting plasma ASM is protective in a mouse model of Alzheimer’s disease - Choi, Byung Jo; Park, Min Hee; Park, Kang Ho; Han, Wan Hui; Yoon, Hee Ji; Jung, Hye Yoon; Hong, Ju Yeon; Chowdhury, Md Riad; Kim, Kyung Yeol; Lee, Jihoon; Song, Im Sook; Pang, Minyeong; et al. (Nature Communications, 2023)
Acid sphingomyelinase (ASM) has been implicated in neurodegenerative disease pathology, including Alzheimer’s disease (AD). However, the specific role of plasma ASM in promoting these pathologies is poorly understood. Herein, we explore plasma ASM as a circulating factor that accelerates neuropathological features in AD by exposing young APP/PS1 mice to the blood of mice overexpressing ASM, through parabiotic surgery. Elevated plasma ASM was found to enhance several neuropathological features in the young APP/PS1 mice by mediating the differentiation of blood-derived, pathogenic Th17 cells. Antibody-based immunotherapy targeting plasma ASM showed efficient inhibition of ASM activity in the blood of APP/PS1 mice and, interestingly, led to prophylactic effects on neuropathological features by suppressing pathogenic Th17 cells. Our data reveals insights into the potential pathogenic mechanisms underlying AD and highlights ASM-targeting immunotherapy as a potential strategy for further investigation.
CRIS-Team Scopus Importer:2023-04-07